PENGARUH INTERPERSONAL BASED MEDICAL SERVICE ENCOUNTERS TERHADAP SERVICE QUALITY , PATIENT SATISFACTION AND PATIENT TRUST - Aprillia Rio Fathia (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2014)
This study aimed to examine the effect of Interpersonal Based Medical Service Encounters on Service Quality, Patient Satisfaction and Patient Trust. This study used a non-probability sampling with purposive sampling technique in which 200 respondents experienced patients in the ARF beauty care clinic and dental clinic serve as a sample. Analysis tool used is the method of data analysis used in this study is a structural equation model (SEM) with the AMOS program uses.From the results of this research is that the factors that can drive the satisfaction of clinic attendees are factors of service quality and service medical encounters need to consider these three to be able to drive satisfaction patient. Service quality factors, gave the need for greater attention to the factors courtesy of the staff to the patients in which this can be done by providing training and guidance is also well to the staff, especially how to be nice and polite to the patient clinic. For future studies it is advisable to increase the number of samples, variables used, and applied inother service industries.Keywords: Interpersonal Encounters.Service Based Medical Service Quality, Patient Satisfaction,Patient Trust.